FORMATION OF NANOCRYSTAL STATE IN DETAILS OF CARBON STRUCURAL STEELS - A. A. Andrushevich; G. I. Aniskovich; p L. Kantor; D. V. Kuchuk (Литьë и металлургия, 2018)
The conditions of formation of the nanocrystal state of the structure in carbon steels are considered in the article. The methods of research and experimental data on the microstructural structure of the strengthened parts of the working bodies of agricultural machinery made from carbon steels of the lowered hardenability are given. It is shown that pulsed quenching and low tempering provides of steel products with fragmented nanocrystal structure of the martensite. Fragmentation of martensite grains in carbon structural steels during heat treatment of parts significantly increases their mechanical characteristics.